EVALUASI PENGGUNAAN OBAT GASTRITIS PADA PASIEN RAWAT INAP DI RS GRANDMED LUBUK PAKAM TAHUN 2020 - Mayasari, Dini; Hutahean, Delfi Mutiara; Octora, Debi Dinha (Jurnal FARMASIMED (JFM), 2021)
Gastritis is a disease caused by the bacterium Helicobacter phylory, this first gastritis drug, namely Antacids, Omeprazole, and Ranitidine. The increasing number of Gastritis patients from 2019 to 2020 at Grandmed Lubuk Pakam Hospital is encouraging researchers to conduct this study. The purpose of this study was to determine the description of the use of Gastritis drugs and the rationality of the use of Gastritis medications in Gastritis patients at Grandmed Lubuk Pakam Hospital in 2019. This study was a descriptive (non-experimental) study with retrospective data collection taken from patient medical records. Gastritis at Grandmed Lubuk Pakam Hospital. Data were collected using a purposive sampling technique in accordance with the inclusion criteria and exclusion criteria using the Data Collection Sheet. The number of samples used in this study were 64 medical records of patients diagnosed with gastritis. Data analysis was performed using Univariat with the help of SPSS. Results of distribution of duration of treatment data for which most patients undergo treatment. And the number of Chronic Diseases suffered by Diarrhea patients is 20 patients (31.2%). All three have a significant relationship with patient care outcomes. While in the age range 31-60 years, 45 people (70.3%) affected by gastritis. and The results of evaluating the rationality of treatment for gastritis are the right indications (96.9%), (62 patients), 100% correct patients (64 patients), the right medication by (96.9%) (62 patients), and the correct dosage 100% correct (64).